Production of three-dimensional quantum dot lattice of Ge/Si core–shell quantum dots and Si/Ge layers in an alumina glass matrix. (20th January 2015) - Buljan, M; Radić, N; Sancho-Paramon, J; Janicki, V; Grenzer, J; Bogdanović-Radović, I; Siketić, Z; Ivanda, M; Utrobičić, A; Hübner, R; Weidauer, R; Valeš, V; et al.
Abstract: We report on the formation of Ge/Si quantum dots with core/shell structure that are arranged in a three-dimensional body centered tetragonal quantum dot lattice in an amorphous alumina matrix. The material is prepared by magnetron sputtering deposition of Al2 O3 /Ge/Si multilayer. The inversion of Ge and Si in the deposition sequence results in the formation of thin Si/Ge layers instead of the dots. Both materials show an atomically sharp interface between the Ge and Si parts of the dots and layers. They have an amorphous internal structure that can be crystallized by an annealing treatment. The light absorption properties of these complex materials are significantly different compared to films that form quantum dot lattices of the pure Ge, Si or a solid solution of GeSi. They show a strong narrow absorption peak that characterizes a type II confinement in accordance with theoretical predictions. The prepared materials are promising for application in quantum dot solar cells.